IDIOM DALAM SERIAL FILM JOHN WICK KARYA CHAD STAHELSKI - Wowor, Jesika; Pamantung, Rina P.; Sigarlaki, Stephani J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â  Â This research is entitled â€œIdioms in the Serial Film John Wick by Chad Stahelskiâ€. The aims of this research are to identify and classify the kind of idioms, as well as to analyze and describe the meaning of idioms in the serial film John Wick by Chad Stahelski. The descriptive method is used in this research. The data were collected from the film John Wick Series 1, 2 and 3, then analyzed based on the theory of Fernando (1996) and Heasley (2007). The result of this research shows that idioms can be found in three kinds. The idioms are pure idioms, semi pure idioms and literal idioms. The meaning of idioms cannot be understood if translated literally but idioms can be understood through the context being discussed. This research can provide knowledge about the meaning of idioms in semantic studies, especially for readers. It also can help students of the Faculty of Humanities, especially students majoring in English Department to examine idioms in using different objects. This research can be used as a reference for further research as well.Key Words: Idioms, Form and Meaning, The Series Film John Wick, Semantic Analysis.